2020
DOI: 10.1186/s12934-020-01476-0
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic engineering of Saccharomyces cerevisiae for high-level production of gastrodin from glucose

Abstract: Background The natural phenolic glycoside gastrodin is the major bioactive ingredient in the well-known Chinese herb Tianma and is widely used as a neuroprotective medicine in the clinic. Microbial production from sustainable resources is a promising method to replace plant extraction and chemical synthesis which were currently used in industrial gastrodin production. Saccharomyces cerevisiae is considered as an attractive host to produce natural plant products used in the food and pharmaceutical fields. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified an error in acknowledgement section. The correct acknowledgement is given below.…”
Section: Correction To: Microb Cell Fact (2020) 19:218 Https://doiorg/101186/s12934-020-01476-0mentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified an error in acknowledgement section. The correct acknowledgement is given below.…”
Section: Correction To: Microb Cell Fact (2020) 19:218 Https://doiorg/101186/s12934-020-01476-0mentioning
confidence: 99%
“…Author details 1 Tianjin Institute of Industrial Biotechnology, Chinese Academy of Sciences, Tianjin 300308, China. 2 Key Laboratory of Systems Microbial Biotechnology, Chinese Academy of Sciences, Tianjin 300308, China.…”
Section: Publisher's Notementioning
confidence: 99%
“… 14 , 15 A few important phenolic glycosides have been successfully synthesized in microorganisms by designing artificial pathways. 16 , 17 In the case of salicin production, microbial synthesis would offer an alternative route in addition to direct extraction from plants.…”
Section: Introductionmentioning
confidence: 99%
“… 26 In recent years, carboxylic acid reductases have demonstrated significant potential to reduce aromatic acids to produce aromatic aldehydes and aromatic alcohols in microorganisms. 17 , 20 , 27 , 28 The synthesis of salicylic alcohol in E. coli was further achieved by introducing a carboxylic acid reductase [carboxylate reductase (CAR) from Mycobacterium marinum ( M. marinum )]. 20 The biosynthetic pathway of salicylic acid from chorismate catalyzed by a salicylate synthase was also known in the biosynthesis of yersiniabactin oramychelin.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, great efforts have been made to regenerate UDPG in situ , aiming reduction of the UDPG supply cost in the microbial host. Recent research indicated that Saccharomyces cerevisiae (baker’s yeast), a Generally Regarded As Safe (GRAS) organism, might be a promising whole-cell biocatalyst host advantageous for the production of valuable glycosides including dietary supplements and pharmaceuticals. S. cerevisiae holds a cytoplasmic pool of UDP glucose (UDPG) generated by the endogenous biosynthetic pathway involving phosphoglucomutase 1 (PGM1), phosphoglucomutase 2 (PGM2), and UDP-glucose pyrophosphorylase 1 (UGP1) (Figure B) .…”
Section: Introductionmentioning
confidence: 99%